Investigation of the effects of direct current stimulation on Parkinson disease in vitro (Annals of Medical Research, 2023)
Aim: Parkinson’s disease (PD) is a progressive, neurodegenerative disease characterized by the loss of dopaminergic neurons. Multiple possible mechanisms such as oxidative stress, mitochondrial dysfunction or excitotoxicity caused by glutamate are thought to mediate neuronal loss in PD. It is stated that transcranial direct current stimulation (tDCS) has positive effects on PD, but underlying mechanisms are still largely undefined. So, in this study, the effects of tDCS on PD and the relationship of these effects with glutamate and NMDA levels were investigated.Materials and Methods: To induce the PD model, 6-OHDA (200 µM) was administered to SH-SY5Y cells for 24 hours. Electrical stimulation was applied to the SH-SY5Y cells at 20 minutes and 7 hours after 24 hours. The effect of tDCS on cell viability was measured by MTT 3-(4, 5-Dimethylthiazol-2-yl) method. Glutamate and NMDA receptor levels were measured using commercial kit.Results: 6-OHDA increases cell death in SH-SY5Y cells, while electrical stimulation reverses this effect. While 6-OHDA increased the glutamate level, tDCS therapy reversed this effect. There is no significant difference between the groups in NMDA levels.Conclusion: Our findings suggest that tDCS can be a functional therapy on PD by reducing glutamate toxicity.
Keywords: Parkinson’s disease; Glutamate; NMDA; Transcranial direct current stimulation; SH-SY5Y cell